Peripheral circular RNAs hsa_circ_0075436 and hsa_circ_0005729 as diagnostic and prognostic biomarkers in acute ischemic stroke: expression profiles and mechanistic insights - Jiang, Wenqun; Chen, Weidong; Lin, Shihao; Hou, Pinpin; Jin, Yichao; Zhang, Xiaohua; Wu, Hui; Gao, Li; Hu, Qin (Frontiers in Molecular Biosciences, 2025)
IntroductionCircular RNAs (circRNAs) are a class of stable, conserved, and tissue-specific non-coding RNAs that have shown potential as diagnostic and prognostic biomarkers in acute ischemic stroke (AIS). However, their expression and functional roles in peripheral blood mononuclear cells (PBMCs) remain largely unexplored.MethodsWe performed whole transcriptome RNA sequencing on PBMC samples from AIS patients (n = 5) and matched healthy controls (n = 5). The top 10 differentially expressed circRNAs were validated by qRT-PCR in a validation cohort (n = 60), and two consistently dysregulated circRNAs were further validated in a larger replication cohort (n = 288). Functional enrichment analysis and competing endogenous RNA (ceRNA) network construction were conducted to explore potential regulatory mechanisms.ResultsTwo circRNAs, hsa_circ_0075436 and hsa_circ_0005729, significantly decreased in PBMCs of AIS patients. The expressive levels negatively correlated with NIH Stroke Scale (NIHSS) scores at admission and discharge. Receiver operating characteristic (ROC) curve analysis demonstrated their strong diagnostic performance. Bioinformatics analyses and qRT-PCR further suggested that hsa_circ_0005729 may influence BBB disruption and peripheral immune suppression in AIS via hsa-miR-1301/COL1A1 axis.ConclusionHsa_circ_0075436 and hsa_circ_0005729 are promising PBMC-derived biomarkers for the diagnosis and prognosis of AIS.